Leadership challenges of directors of emergency medicine: An Australasian Delphi study. (29th October 2019) - Rixon, Andrew; Wilson, Samuel; Hussain, Sairah; Terziovski, Mile; Judkins, Simon; White, Peter
Abstract: Objective: Emergency medicine (EM) is an emerging profession with complex clinical and leadership demands. However, studies of leadership in EM are in their infancy. The present study makes a novel contribution to empirical research in this area by examining the leadership challenges faced by Australasian directors of emergency medicine (DEMs). Methods: An online Delphi study was conducted with 87 Australasian DEMs. To structure the process, participants were sorted into four panels reflecting their leadership experience and geographical location. Using a three‐phase Delphi process, participants were guided through the process of brainstorming leadership challenges, narrowing down these challenges, and ranking these challenges from most to least important. Results: Four leadership challenges were shared across all panels, regardless of experience and location; namely, administrative overload, overcrowding and access block, managing challenging colleagues and engaging with hospital executive. However, the low consensus achieved within and across panels highlights the complexity of leadership in EM and cautions against simplistic approaches to addressing leadership challenges. Conclusion: The recommendation for DEMs is that they need to engage in programmes which will support the development of the leadership and non‐clinical skills required to enable them to cope with responsibilities of hybrid role of physician‐leader. The development and delivery of specialised leadership programmes attuned to the hybridity of the director role and the complexity of hospitals is vital for ensuring high‐quality patient care and successful running of EDs.